Undisturbed Universal Pendulum Device for Determining Spatial Position of Aircraft - Karimli, T.I. (Herald of Azerbaijan Engineering Academy, 2023)
The article gives a review of devices for determining the spatial position of static and dynamic objects for various purposes, and principles of their operation are investigated. The state of a disturbed classical pendulum in determining the spatial position of objects under the influence of accelerating motion and the classical solution to eliminate the impact of the diturbance are considered. Variants of an undisturbed universal-purpose mechanical pendulum are presented.